Stories of mental health, resilience and recovery - Costello, Amanda; Carson, Jerome (Emerald points., 2025)
Mental health struggles affect millions, yet personal stories of resilience and recovery often go unheard. In a world that still stigmatises mental health challenges, first-person narratives offer powerful insights into the realities of trauma, healing, and hope. These stories not only illuminate the lived experiences of individuals navigating mental distress but also challenge dominant societal perceptions, fostering empathy, connection, and a deeper understanding of the human condition. Stories of Mental Health, Resilience and Recovery is a compelling exploration of personal strength in the face of adversity. This volume brings together seven deeply moving first-person accounts, highlighting the resilience of individuals who have faced trauma, discrimination, and profound psychological struggles. Taking an autoethnographic approach, these narratives are gathered with empathy, ethical sensitivity, and a commitment to amplifying voices too often marginalised. By weaving together these powerful testimonies, this work not only provides insight into personal journeys of recovery but also challenges societal norms, encourages self-reflection, and advocates for greater inclusion and justice for those experiencing mental health difficulties. Offering invaluable perspectives for individuals with similar experiences, as well as educators, policymakers, and mental health professionals, Stories of Mental Health, Resilience and Recovery is an essential read for anyone seeking to deepen their understanding of resilience, recovery, and the transformative power of storytelling.